Libros en inglés sobre América Latina - de Nuestra América, Temas (2018)
Politics and Social Change in Latin America: the Distinct TraditionPolitical Change in Central America. Internal and External DimensionsThe End and the Beginnig: the Nicaraguan RevolutionRevolution in Central America